Captain Everill's Error: Mapping the Upper Strickland River in Papua and New Guinea, 1885–1979. Issue 3 (3rd July 2018) - Dwyer, Peter D.; Minnegal, Monica
ABSTRACT: An error dating from 1885 in mapping the upper Strickland River, Papua New Guinea, was reinforced and extended by government officer Charles Karius in 1929 when reporting results from a lengthy exploratory patrol. Detailed maps produced by the US Army and the Royal Australian Survey Corps in, respectively, 1942 and 1966 perpetuated these errors. It was not until 1979, with release of a series of 1:100, 000 topographic maps, that long-standing errors were finally put to rest. Throughout these years, the contributions of well-informed people tended to be ignored in favour of the opinions of those whose status implied authority.